Fixed-bed Biomass Combustor: Air Mass Flow Rate and Particles Size Effects on Ignition Front Propagation of Solid Olive Waste. Issue 2 (25th January 2022) - Elorf, Abdallah; Bakhatar, I.; Asbik, M.; Sarh, B.; Gillon, P.
ABSTRACT: This study analyzed the biomass flame behavior in a vertical fixed-bed combustor. Experimental tests were carried out with olive waste (OW) as solid fuel in different combustion conditions. The effect of air mass flow (AMF), particles size and bulk density on mass ignition rate (MIR), maximum temperature, ignition front velocity (IFV) and bed height was investigated. Comparison with other experimental results given in the literature is carried out. The results showed the strong effect of AMF detected on the conversion behavior of tested biomass. It is shown that the increase in the AMF distinguishes three different phases. Firstly increasing in maximum temperature, IFV and MIR, it is the acceleration phase. Secondly corresponding to convective cooling phase where all parameters decrease lightly and the last quasi-constant phase, correspond to the reaction-limited phase. Finally, The five experimental tests with different particles size and various bulk densities were conducted. It is shown that the large particles have higher IFV than small particles.